A coculture model of the lung–blood barrier: The role of activated phagocytic cells. Issue 1 (February 2015) - Luyts, Katrien; Napierska, Dorota; Dinsdale, David; Klein, Sebastian G.; Serchi, Tommaso; Hoet, Peter H.M.
Graphical abstract